Triatoma petrocchiae (Hemiptera, Reduviidae, Triatominae): A Chagas disease vector of T. brasiliensis species complex associated to reptiles - Lilioso, Maurício; Pires-Silva, Dayane; von Hertwig Mascarenhas Fontes, Fernanda; Oliveira, Jader [UNESP]; da Rosa, João Aristeu [UNESP]; Vilela, Roberto V.; Folly-Ramos, Elaine; Almeida, Carlos Eduardo (Elsevier, 2020)
In semi-arid areas of northeastern Brazil, Chagas disease vectors of Triatoma brasiliensis species complex comprise a monophyletic group of kissing bugs that inhabit rock outcrops. Most of them exhibit allopatric or parapatric distribution; the exception is T. petrocchiae, which is found in cohabitation with T. brasiliensis in rock outcrops. We used vertebrate mitochondrial gene sequencing applied to DNA isolated from bug midgut to identify the insect blood meal sources via BLAST procedure. Fourteen sylvatic insects from four geographic districts in the states of Rio Grande do Norte and Paraíba had their blood meal sources detected. While T. brasiliensis is recorded to be associated mainly (52–71%) with rodents, T. petrocchiae samples were strongly associated (86%) with reptiles of Tropidurus and Hemidactylus genera. We suggest that T. petrocchiae is the single member within this complex to be associated with reptiles, indicating a distinct niche occupation related to the trophic resources.
Keywords: Insect vector; Niche occupation; Triatomine ecology; Trophic resource